ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PEMBAGIAN DI KELAS IV SEKOLAH DASAR - Deswita, Hera (Edu Research, 2015)
Learning mathematics operation which consist of addition, subtraction,multiplication, and division are the basic skill for students. In fact mostly student didmistake in division. The purpose of this research are 1) to know type of studentsmistake in doing division test, 2) to know the factor that influence the student mistakein mathematics division test.This research used qualitative descriptive design. Theresearcher explored and described types of students mistake in doing division test andfactor that influence the student mistake in mathematics division test. The subject ofthe research consist of three students that have difference cognitive skill; high, middleand low. The finding showed that type of students mistake in doing division test weremisusedstrategy and miscalculated in students worksheet. However the factor thatinfluence the student mistake in mathematics division test is psychological factor ;student do not like mathematics and students cannot recognize multiplicationindependentl.